2011
DOI: 10.1007/s10616-011-9398-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and differentiation potential of an equine amnion-derived stromal cell line

Abstract: Stem cells represent an important tool in veterinary therapeutic field such as tissue engineering. In the present study, equine amnion-derived mesenchymal stromal cells were investigated for applications in veterinary science as an alternative source to bone marrow mesenchymal stem cells and adipose stem cells. Amnion stromal cells isolation and characterization protocol is described; the in vitro cell growth rate was calculated by measuring viable cell number over 20 days. The expression of stem cell markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
(32 reference statements)
1
7
0
1
Order By: Relevance
“…Many reports demonstrated that amnion-derived cells have potential to differentiate into cells of mesenchymal lineages in vitro in many species such as bovine , canine (Park et al 2012), feline (Rutigliano et al 2013), chicken (Gao et al 2012), rat (Marcus et al 2008) and equine (Coli et al 2011;Violini et al 2012;Seo et al 2013). In support to these reports, we successfully differentiate the buffalo mesenchymal stem cell-like cells derived from term placenta into adipogenic, chondrogenic and osteogenic cells of mesodermal lineage (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Many reports demonstrated that amnion-derived cells have potential to differentiate into cells of mesenchymal lineages in vitro in many species such as bovine , canine (Park et al 2012), feline (Rutigliano et al 2013), chicken (Gao et al 2012), rat (Marcus et al 2008) and equine (Coli et al 2011;Violini et al 2012;Seo et al 2013). In support to these reports, we successfully differentiate the buffalo mesenchymal stem cell-like cells derived from term placenta into adipogenic, chondrogenic and osteogenic cells of mesodermal lineage (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Recently, Yamahara et al (2014) reported that mesenchymal stem cells isolated from human amniotic tissue have an angiogenesis potential. In animals, amnion-derived stem cells have potential of differentiation into multilineage mesenchymal cell types in many species such as bovine , canine (Park et al 2012), feline (Rutigliano et al 2013), chicken (Gao et al 2012), rat (Marcus et al 2008) and equine (Coli et al 2011;Violini et al 2012;Seo et al 2013). This makes these cells more suitable candidates for cell therapy with less chances of immune-rejection (Lovati et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Trilineage differentiation potential has been described for equine MSCs derived from bone marrow (74), adipose tissue (97, 98), peripheral blood (99, 100), umbilical cord blood (101), umbilical cord matrix (82), gingiva and periodontal ligament (90), amnion (88) and amnion fluid (84), although the extent of differentiation varied based on the cell source and the differentiation protocols used. Adipogenic differentiation of equine MSCs strongly depends on the components of the differentiation media (102).…”
Section: In Vitro Characterization Of Equine Stem Cellsmentioning
confidence: 99%
“…Recently, Yamahara et al (2014) reported that mesenchymal stem cells isolated from human amniotic tissue have an angiogenesis potential. In animals, amnion-derived stem cells have potential of differentiation into multilineage mesenchymal cell types in many species such as bovine , canine (Park et al 2012), feline (Rutigliano et al 2013), chicken (Gao et al 2012), rat (Marcus et al 2008) and equine (Coli et al 2011;Violini et al 2012;Seo et al 2013). Further, the amnion derived MSCs are reported to express certain key pluripotency markers including OCT4 .…”
Section: Introductionmentioning
confidence: 99%